Kaum Muda, Intoleransi, dan Radikalisme Agama - Zuly Qodir (Universitas Gadjah Mada, 2016)
Youth, Intolerance, and Radicalism are serious problems facing Indonesia and other countries including in the Middle East. This phenomenon has sprung up over the last five years with various events that have surfaced. There are many reasons for the emergence of radicalism among young people and intolerance. However, there are several alternatives also to reduce the movement of intolerance and radicalism of youth. Religious movements that come from mass organizations such as Muhammadiyah and NU can be expected to reduce it. The most phenomenal phenomenon is the emergence of ISIS Islamic state of Iraq and Syria with various violent activities in Iraq and Syria affecting religious life in Indonesia. The movement of intolerance and radicalism arises because of the lazy tolerance. The essay below wants to reflect on the continuous occurrence of terrorist acts of terrorism radicalism in our country. The following essays are based largely on literature reviews written on the basis of reports or by others, as well as observations from the authors